2009
DOI: 10.1111/j.1600-0854.2008.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Dictyostelium Tom1 Participates to an Ancestral ESCRT‐0 Complex

Abstract: Sorting of ubiquitinated proteins to multivesicular bodies (MVBs) in mammalian cells relies on proteins with a Vps27/ Hrs/STAM (VHS) domain. Here, we show that the amoeba Dictyostelium presents only one protein with a VHS domain: DdTom1. We demonstrate that the VHS domain of DdTom1 is followed by a Golgi-localized, g-earcontaining, ADP-ribosylation-factor-binding and Tom1 (GAT) domain that binds ubiquitin, and by a nonconserved C-terminal domain that can recruit clathrin, EGFr pathway substrate 15 and tumor su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 76 publications
3
67
0
Order By: Relevance
“…In order to test this possibility, we resorted to lipid overlay experiments using PIP Strips TM . Consistent with results obtained with Dictyostelium discoideum DdTOM1, the only VHS-domain-containing protein in the amoeba (Blanc et al, 2009), we found that the VHS domain of the human TOM1 interacted with the phosphatidylinositol monophosphates ( Fig. 3A, VHS).…”
Section: Tom1 Is Enriched On Signaling Endosomes In Ipgd-expressing Csupporting
confidence: 79%
See 2 more Smart Citations
“…In order to test this possibility, we resorted to lipid overlay experiments using PIP Strips TM . Consistent with results obtained with Dictyostelium discoideum DdTOM1, the only VHS-domain-containing protein in the amoeba (Blanc et al, 2009), we found that the VHS domain of the human TOM1 interacted with the phosphatidylinositol monophosphates ( Fig. 3A, VHS).…”
Section: Tom1 Is Enriched On Signaling Endosomes In Ipgd-expressing Csupporting
confidence: 79%
“…3B, VHS). This is in contrast to DdTOM1, which showed a clear preference for PI3P and no binding to PI5P (Blanc et al, 2009). Preferential binding of the VHS to PI5P was further confirmed in a liposome flotation assay with liposome containing phosphatidylcholine:phosphatidylethanolamine and PI3P, PI4P or PI5P (Fig.…”
Section: Tom1 Is Enriched On Signaling Endosomes In Ipgd-expressing Cmentioning
confidence: 93%
See 1 more Smart Citation
“…ESCRT-0 appears to be specific to the opisthokonts (metazoa and fungi) and is absent from Dictyostelium discoideum, a member of their sister lineage the Amoebozoa, as well as from plants (Winter & Hauser, 2006;Leung et al, 2008;Field & Dacks, 2009). However D. discoideum contains instead a minimal, possibly ancestral ESCRT-0 in which DdTom1 interacts with ubiquitin, clathrin and the ESCRT-1 protein Tsg101 (Blanc et al, 2009). MVBs were also recently identified in the basal amoebozoan Breviata anathema, strengthening the conclusion that the ESCRTs' are a common feature of this supergroup (Herman et al, 2011).…”
Section: Evolutionary Conservation Of Escrts'mentioning
confidence: 99%
“…Not only do many of the genes encoding ESCRT subunits appear to have caretaker functions, with mutations being linked to both cancer and neurological disorders, these genes also have an origin pre-dating the metazoan lineage (reviewed by Ilievska et al, 2011). Model organisms, such as the amoeba, Dictyostelium discoideum (Annesley & Fisher, 2009;Williams RS et al, 2006), can therefore be used to study the fundamental molecular roles of these proteins (Blanc et al, 2009;Mattei et al, 2006). Overall, the evolutionary age of cancer genes parallels their role in human cancer etiology (Fig.…”
Section: Evolution Of Cancer Genesmentioning
confidence: 99%